DEVELOPMENT OF PERSONALIZED LEARNING MANAGEMENT SYSTEM WITH ADAPTIVE FEATURES OF MICROTEACHING AND REFLECTIVE PRACTICE COURSES FOR PRESERVICE TEACHERS: PENGEMBANGAN SISTEM MANAJEMEN PEMBELAJARAN PERSONALISASI DENGAN FITUR ADAPTIF MIKROTEACHING DAN KURSUS PRAKTIK REFLEKTIF BAGI GURU PRAJABAT - Imro’atul Husna Afriani; St. Shabibatul Rohmah; Dian Arief Pradana (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
Personalization in learning management system (LMS) is important as a learning environment to adjust the learning experience to the individual needs of students. This research and development aims to develop and implement an adaptive Learning Management System (LMS) for the Microteaching and Reflective Practice course at FKIP Untag Banyuwangi. This LMS is designed to personalize students' learning experiences according to individual needs, increasing the effectiveness and relevance of teaching. Microteaching gives prospective teachers the opportunity to practice teaching on a small scale, while reflective practice encourages them to analyze and improve teaching methods. The use of LMS allows students to study independently before face-to-face classes and reflect on their learning more deeply. This research and development focuses on creating a personalized learning environment using adaptive techniques that are valid and feasible to use as a student learning environment. This research and development uses the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model to develop learning resources that can be accessed according to student needs. The results of the study indicate that the adaptive LMS developed is valid and feasible to use as a learning environment for the Microteaching and Reflective Practice course. This LMS effectively facilitates personalization of learning and supports reflection and improvement of student teaching skills.